Meridional gradients in aerosol vertical distribution over Indian Mainland: Observations and model simulations. (January 2016) - Prijith, S.S.; Suresh Babu, S.; Lakshmi, N.B.; Satheesh, S.K.; Krishna Moorthy, K.
Abstract: Multi-year observations from the network of ground-based observatories (ARFINET), established under the project 'Aerosol Radiative Forcing over India' (ARFI) of Indian Space Research Organization and space-borne lidar 'Cloud Aerosol Lidar with Orthogonal Polarization' (CALIOP) along with simulations from the chemical transport model 'Goddard Chemistry Aerosol Radiation and Transport' (GOCART), are used to characterize the vertical distribution of atmospheric aerosols over the Indian landmass and its spatial structure. While the vertical distribution of aerosol extinction showed higher values close to the surface followed by a gradual decrease at increasing altitudes, a strong meridional increase is observed in the vertical spread of aerosols across the Indian region in all seasons. It emerges that the strong thermal convections cause deepening of the atmospheric boundary layer, which although reduces the aerosol concentration at lower altitudes, enhances the concentration at higher elevations by pumping up more aerosols from below and also helping the lofted particles to reach higher levels in the atmosphere. Aerosol depolarization ratios derived from CALIPSO as well as the GOCART simulations indicate the dominance of mineral dust aerosols during spring and summer and anthropogenic aerosols in winter. During summer monsoon, though heavy rainfall associated with the Indian monsoon removes large amounts of aerosols, the prevailing southwesterly winds advect more marine aerosols over to landmass (from the adjoining oceans) leading to increase in aerosol loading at lower altitudes than in spring. During spring and summer months, aerosol loading is found to be significant, even at altitudes as high as 4 km, and this is proposed to have significant impacts on the regional climate systems such as Indian monsoon. Highlights: Ground based and space borne observations supported by transport model simulations. Meridional increase in the vertical spread of aerosols over India during spring. Dominance of mineral dust aerosols during spring and summer at higher altitudes.